The Use of Learning English Webtoon Comics to Improve the Students' Speaking Ability - Merita, Rona; Wastyanti, Afina; Habibah, Aina Noor; Syahroni, Atour Rohman (Journal of Instructional and Development Researches, 2023)
Considering that Webtoon is an innovative media in teaching reading comprehension. And The Question Is How can the use of English comic improve the ability of students?. Teachers should know how to use Webtoon and how to connect students into virtual classroom that can give some advantages either for teacher or students. For teacher, social application like Webtoon can make teachers help students to interested and teach how to use their android, computer and their free time by reading. It can be suitable process where the process of teaching and learning is not limited to classroom for meeting only. For students, it can be new experience for them to learn digitally and virtually. This strategy supported by researchers. The research design of this study is Classroom Action Research (CAR). This study uses Classroom Action Research (CAR) as the design research, because it attempts to overcome students’ problem in their teaching-learning activities. There are 2 cycles to get a good score to test student, the first is Cycle 1 Quality Time that contains post-test webtoon, the second is Cycle 2 Good As New that contains evaluation webtoon. accordance with the objective of the research was to improve students’ ability in speaking through the use of English comic. The results of this research on English subjects can be concluded that English learning is still conventional, In post-test of cycle 1, the results were established from quantitative and qualitative data. Quantitatively, the students score were improved but still categorized unsuccessful because only 11 students who improved and passed the MPG. In post-test of cycle 2, the results of the research were gained from both quantitative and qualitative data. Quantitatively, it showed the students got higher score of pronunciation test after using this technique. There are 31 students were categorized successful and passed the MPG. It means that the students’ speaking ability was improved. The data also strengthened by the qualitative data from the observation and the interview with the students and the teacher. It shows that they feel more better in speaking using comic webtoon as media.